(untitled) (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to conceptually analyze the role of the Local Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD) in improving Financial Reporting Quality FRQ of local governments by synthesizing theories regulations and prior studies related to public sector information systems and financial reporting. This research adopts a conceptual paper method focusing on the development of a theoretical framework that explains the relationship between SIPD implementation and financial reporting quality dimensions namely relevance reliability comparability and understandability by aligning Government Accounting Standards with internationally recognized qualitative characteristics of financial reporting as emphasized by the Financial Accounting Standards Board FASB. The analysis indicates that SIPD as an integrated and mandatory national information system has strong potential to enhance FRQ through improved data integration standardized financial reporting processes and strengthened audit trails across local government entities. Looking forward this study expects that consistent SIPD implementation supported by adequate human resource competence reliable information technology infrastructure and regulatory stability will contribute to more transparent accountable and decision useful local government financial reports thereby strengthening public trust and supporting effective fiscal governance at the regional level. Conceptually this paper provides a theoretical foundation for future empirical research and policy evaluation regarding SIPD and its long term impact on the quality of local government financial reporting.